2019
DOI: 10.5539/elt.v12n4p73
|View full text |Cite
|
Sign up to set email alerts
|

Improving Oral Communicative Competence in English Using Project-Based Learning Activities

Abstract: The quasi-experimental study investigated the effectiveness of using project-based learning (PjBL) activities as a teaching strategy in improving the oral communicative competence of Malaysian English language learners. The participants included 44 diploma students enrolled in a Communicative English course at a technical college in the Peninsular Malaysia, who were purposely selected for the study. The intervention comprised a 12-week lessons taught using PjBL teaching strategy and centred on eight PjBL activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…One of learning methods that can be used to make learning interesting and can stimulate students to be active in speaking is the projectbased learning method or Project Based Learning (PBL). There have been several previous studies which have shown the effectiveness of this model in improving speaking skills in learning foreign languages (Bakar, Noordin, & Razali, 2019;Wuryantari Winasih, Cahyono, & Ananto Prayogo, 2019). The findings of the study indicate that the Project Based Learning model provides the opportunity for instructors to manage learning in the classroom by involving project work that contains complex tasks based on questions and problems that are very challenging and guides students to design, solve problems, make decisions, conduct investigative activities, as well as provide students the opportunity to work independently.…”
Section: Introductionmentioning
confidence: 99%
“…One of learning methods that can be used to make learning interesting and can stimulate students to be active in speaking is the projectbased learning method or Project Based Learning (PBL). There have been several previous studies which have shown the effectiveness of this model in improving speaking skills in learning foreign languages (Bakar, Noordin, & Razali, 2019;Wuryantari Winasih, Cahyono, & Ananto Prayogo, 2019). The findings of the study indicate that the Project Based Learning model provides the opportunity for instructors to manage learning in the classroom by involving project work that contains complex tasks based on questions and problems that are very challenging and guides students to design, solve problems, make decisions, conduct investigative activities, as well as provide students the opportunity to work independently.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on implementation of Project Based Learning in enhancing language acquisition, with positive impact. Most of the studies affirmed that using PBL approach in learning helps the pupils to develop their language skills (Azura et al, 2012;Newprasit & Seepho 2015;Shanthi et al 2015;Zhang, 2015) as cited in Bakar et al (2019). However, there are limited studies to explore the implementation of Gold Standard Project Based Learning in Malaysian classroom (Aiedah & Lee, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…They help learners to communicate, collaborate and engage with each other to perform their goals. Because of the importance of PBL and PL in teaching and learning English language and its skills, researchers conducted studies through using them at the university level such as Eid (2008), Poonpon (2011) ,Al-Sabagh (2012 ,Al-Neguly (2013) , Marwan (2015), Shehata (2015) , El-Shehawy (2017) , Kimsesiz, Dolgunsöz &Konca (2017) , Mahmoud (2017) , Pilten, Pilten & Sahinkaya (2017) , Mahasneh & Alwan (2018) ,Carrabba &Farmer (2018) , Duman & Yavuz (2018) , Sirisrimangkorn (2018) , Elsadek (2018) , Zahran (2018) , Abu Bakar, Noordin & Razali (2019) and El-Sayed (2019) .…”
Section: Introductionmentioning
confidence: 99%